A Comparative Analysis of Pronunciation Proficiency among Arabic and English Department Students Using Accent Software - Asmawati, Nur; Nurdin, Nurdin (Institut Agama Islam Negeri Palopo, 2023)
One way to improve pronunciation skills is to use sophisticated technology, namely software that can help reduce accent errors. In this study we used ELSA Speak software which is an application (app) for moderating a non-native English accent. This study aims to determine whether accent reduction software can improve students’ pronunciation abilities. It uses quantitative methods with an experimental research approach. The research was conducted at one of the Islamic universities in Indonesia. We recruited 40 students – 20 from the English department and 20 from the Arabic language department. Their ages are between 19 and 20, and they have been studying English and Arabic within their departments for four semesters. Ten students from each department were allocated to the experimental class, and ten other students from both majors were placed in the control class. The experimental class was taught by researchers using accent reduction software, while the control class was taught by an English teacher using conventional techniques. We used a voice recorder to capture students’ pronunciation. The data were analysed using descriptive analysis and t-test. The results of the study show that the application of accent reduction software as a medium for teaching English pronunciation can improve students’ skills in English pronunciation (t = 3.538, tcalculate> ttable). This software helps students produce English words clearly and easily because they can hear and imitate the sounds it generates. The implication of using the software can help students to imitate native speaker pronunciation and teachers can reduce their efforts in pronouncing native English sounds because the software functions as a pronunciation learning aid